AGAMA SEBAGAI INSTITUSI (LEMBAGA) SOSIAL (Kajian Sosiologi Agama) - Saat, Sulaiman (Inspiratif Pendidikan, 2016)
Religion is a thing that is known, understood, adhered to, and valued in every society at all levels of culture. Thus, religion has become an institution whose existence is recognized by its followers. Religion provides guidelines for the followrs’ behavior, maintains the integrity of the society, and guides the public to hold a social control system (supervision system by society on the followers’ behavior). Conflicts with religious motives are actually caused due to excessive religious fanaticism, especially in social life as well as the lack of understanding of the teachings of their religion.